Health Inequality and Structural Injustice in Indonesia’s National Health Insurance System: A Rawlsian Analysis - Alif Ahmad; Axel Raphael; Zuwanda, Said Sadam; Sahur Ramsay; Diakaridia Fomba (UIN Sunan Kalijaga Yogyakarta, 2025)
This article analyzes structural inequalities in the implementation of the National Health Insurance Program (JKN) in Indonesia using John Rawls’ Difference Principle as a normative framework. Although JKN has achieved near-universal coverage of approximately 98% of the population by 2025, disparities in access, quality, and distribution of healthcare services persist, particularly in remote, border, and archipelagic areas (DTPK). This study employs a normative legal method combined with policy analysis to evaluate whether the institutional structure of Indonesia’s health system has provided optimal benefits for the least advantaged groups. The findings show that unequal distribution of medical personnel, the concentration of specialist doctors in urban areas, and limited primary healthcare infrastructure reflect structural failures that contradict the principle of distributive justice. The JKN system, which is formally universal, has not been able to ensure substantive justice as it continues to reproduce social and geographical inequalities. This article contributes theoretically by integrating Rawls’ Difference Principle into health policy analysis, and practically by offering a justice-based reform framework through affirmative and redistributive interventions, including redistribution of health workers, inequality-based budget reallocation, and the use of health technology to overcome geographical barriers. These findings emphasize that achieving justice in the health system is not sufficient through expanding financial coverage alone, but requires structural transformation oriented towards the most vulnerable groups.